ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI JAGUNG DI DESA OLOBOJU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Talib.S Talib.S; Lien Damayanti; Sulaeman Sulaeman (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
Corn (Zea Mays) is one of the most important cultivated plants in our civilization. Although it mainly refers to the type of crop, corn is also used to refer to some kinds of the same Zeaclan commonly called grasses. This study aimed to determine the amount of income and the feasibility of cor farming located in Oloboju village of  Sigi Biromaru sub district of Sigi District from March to June 2016. Determination of samples was done usingasimple random sampling method.  The samples used in the study were 30 respondents selected from a population of 75 corn growers. The results of the analysis showed that the average production of cornwas 4,666 kg with the average revenue of IDR 12,740,002, while the average of total cost spent by onerespondent farmer was IDR 3,070,341 with an income of IDR 9,669,660.  The value of R/C was4.14 (>1) indicating that the corn farming is feasible to be developed.